Elastic yarns and textiles - Thiel, Jan 1989-; Gries, Thomas 1960- (Hanser, 2025)
This edited work describes and explains the production of elastic textiles from raw material to fiber and yarn, processing, and application. Environmental aspects (e.g., recycling) are also covered. Expert contributions from industry and research present the state of the art and practical new developments in such a way that users from industry and trade can use them in line with market requirements. In addition, trainees and students as well as textile experts are addressed. In terms of textile technology, textile elasticity is the provision of stretch and recovery on demand. It is one of the most important textile properties as it has a direct effect on the overall functionality of many textile products. It is textile elasticity that opens up various areas of application in special and mass-produced products, especially concerning stretch and compression. Many of the clothing textiles produced today, as well as almost all medical textiles, contain special elastic yarns that enable or reinforce textile elasticity. These points are illustrated with practical examples throughout this book. Content: • Introduction to Elastic Yarns and Textiles • Elasticity in the Textile Context • Spinning Technologies for Elastic Yarn Production • State-of-the-Art Elastane Production • Elastic Thermoplastic Polyurethane Yarns • Elastic Polyamide Yarns • Winding of Elastic Yarns • Elastic Combination Yarns • Quality Control of Elastic Yarns • The Market of Elastic Yarns • Weft-Knitted Elastic Fabrics • Warp-Knitted Elastic Fabrics • Woven Elastic Fabrics • Elastic Textiles in the Dyehouse • Elastic Yarns from Renewable Resources • Sorting and Recycling of Elastic Textiles • Elastic Textiles in Medical Technol
Keywords: Elastizität; Struktur; Stoffeigenschaft; Polymere; Faser; Garn; Textilien